Pengenalan Teknologi Metaverse Untuk Siswa SMK Budi Karya Natar - Auliya Rahman Isnain; Ade Dwi Putra; Setiawansyah Setiawansyah (Journal of Engineering and Information Technology for Community Service, 2023)
Metaverse is a virtual world that allows users to connect, communicate, work, play, and transact like in the real world. Metaverse is a virtual world concept that can be owned and filled with various objects and activities like the real world. SMK Budi Karya Natar is an example of a school that has not utilized metaverse technology. So that this is the main goal of the Lecturer Service Team of the Faculty of Engineering and Computer Science, University Teknokrat Indonesia to introduce and provide students with knowledge about the technology and the benefits that will be obtained by using the metaverse technology. The results of the questionnaire on knowledge about metaverse technology that were distributed before the activity and after the activity there was an increase in students knowledge about metaverse technology from knowing by 14% before the PKM activity, after this activity increased to 100% knowing about metaverse technology